Avaliação da atividade antinociceptiva e anti-inflamatória do citronelol em roedores - Brito, Renan Guedes de (2013)
The Citronellol (CT) is an alcoholic monoterpene present in the essential oil of some medicinal plants such as Cymbopogon citratus. Some pharmacological effects such as the antispasmodic and anticonvulsant activities have been described, however it s possible antinociceptive and anti-inflammatory effect is unknown. Thus, the objective of this study was to evaluate the possible antinociceptive and anti-inflammatory action of CT in rodents. Therefore, 362 male Swiss mice (25-35 g) with 2 to 3 months were used. The animals were divided into groups and were treated with CT (25, 50 and 100 mg/kg, i.p.), vehicle (saline solution 0.9% + Tween 80 0.2%, i.p.) or standard drug (i.p.). To evaluate the antinociceptive activity, the animals were submitted to the test of abdomnal constrictions induced by acetic acid (0.85%), the formalin test (1%) and hot plate test. In order to evaluate the effect of CT on orofacial nociception, it was conducted the orofacial test induced by formalin (2%), capsaicin and glutamate. Motor coordination was assessed using the motor coordination test (rota rod) and the spontaneous movement test. The anti-inflammatory activity was evaluated based on the model of carrageenan-induced pleurisy, making up the total leucocyte count. It was also quantified, by using ELISA, TNF-α and nitric oxide generation by macrophages. To determine the central action, the animals were treated with CT, in three doses, or vehicle and, after ninety minutes, were anesthetized, perfused, the brains removed and cut in a cryostat. The brain sections were subjected to immunofluorescence protocol for Fos protein. Results are expressed as mean ± SEM Differences between groups were analyzed by using one way ANOVA test, and followed by Tukey test. Values of p < 0.05 were considered statistically significant. Intraperitoneal administration of CT produced a significant decrease (p < 0.001) of the abdominal constrictions induced by acetic acid. In nociception induced by formalin, the pretreatment with CT caused a significant antinociceptive effect (p <0.01) in both phases of the test. In the hot plate test, the reaction time increased significantly at all doses of CT (p < 0.05 or p < 0.001), while its effect was antagonized by naloxone. In the three orofacial nociception tests, the CT produced a significant decrease (p <0.001) in the face-rubbing time of the orofacial region. No changes were observed in the motor coordination and in the spontaneous movement test. In the evaluation of anti-inflammatory activity, treatment with CT gave rise to a significant decrease (p < 0.01) in total number of leukocytes, decreasing (p < 0.05) the levels of TNF-α and nitric oxide in macrophages (p < 0.05). By immunofluorescence, it was found that CT is able to activate signicantly (p < 0.05) neurons of the olfactory bulb, the piriform cortex, the restrosplenial cortex and the periaqueductal gray. So, it can be concluded that CT has antinociceptive and anti-inflammatory activity and its action is mediated by central and peripheral mechanisms.